Sikap Moderasi Beragama Komunitas Islam dan Kristen: Studi di Kelurahan Tegal Sari Mandala II - Siregar, Einil Sahmadan (Islam & Contemporary Issues, 2022)
It has long been a custom and part of the culture of the Tegal Sari Mandala II Village for the Muslim and Christian populations to practice religious tolerance. The expansion and development of tolerance values and a sense of mutual care, as well as each religious community's awareness of the meaning of diversity and supported with the involvement of local government, community leaders, youth leaders, religious leaders, and of course the existing religious institutions, are all factors that support the establishment of an attitude of religious moderation between the Muslim and Christian communities in the Tegal Sari Mandala II Village. Since the values of religious moderation have been developing for a while and have become part of the local community's tradition and culture, there were no challenges in the Tegal Sari Mandala II Village that prevented the establishment of religious moderation between the Muslim and Christian communities, but there are some grave dangers that exist. The presence of excessive religious zeal and a lot of fake material that is so outlandish that it emerges on various social media and conveys problems related to religious conflicts that cannot be explained might be a barrier to the development of a mindset of religious moderation.